2018
DOI: 10.1093/ijnp/pyy012
|View full text |Cite
|
Sign up to set email alerts
|

A Preclinical Study of Casein Glycomacropeptide as a Dietary Intervention for Acute Mania

Abstract: BackgroundCasein glycomacropeptide is a peptide that lacks phenylalanine, tyrosine, and tryptophan. This profile may enable it to deplete phenylalanine, tyrosine, and tryptophan, and subsequently the synthesis of dopamine and serotonin in the brain. Dopamine- and serotonin-depleting amino acid mixtures have shown promise as acute antimanic treatments. In this study, we explore the depleting effects on amino acids, dopamine and serotonin as well as its actions on manic-like and other behavior in rats.MethodsCas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
1
9
1
Order By: Relevance
“…Increased immobility is associated with a depressive‐like phenotype . The two‐day FST protocol included OF testing to assess locomotor activity, an important cofounder of the FST. On day one of the FST, 4 weeks after the SAB test, rats were acclimatised to the testing room (150 lx) 1 hour prior to testing.…”
Section: Methodsmentioning
confidence: 99%
“…Increased immobility is associated with a depressive‐like phenotype . The two‐day FST protocol included OF testing to assess locomotor activity, an important cofounder of the FST. On day one of the FST, 4 weeks after the SAB test, rats were acclimatised to the testing room (150 lx) 1 hour prior to testing.…”
Section: Methodsmentioning
confidence: 99%
“…In preclinical studies, we found a Tyr and Phe reduction in the blood of 39-56% (Liebenberg et al, 2018). In the study by Sheehan, the reduction was 40-50% as well (Sheehan et al, 1996).…”
Section: Power Analysesmentioning
confidence: 73%
“…In the tap water condition, the plasma Tyr was reduced with 10% and Phe with 3%. In the study from our research group, Tyr was reduced with 50% compared to tap water (Liebenberg et al, 2018).…”
Section: Clinical Studiesmentioning
confidence: 84%
See 1 more Smart Citation
“…S-free fatty acids (FFA) were measured using the in vitro enzymatic colorimetric method assay NEFA-HR(2), which quantifies the concentration of non-esterified fatty acids (FUJIFILM Wako Chemicals Europe GmbH, Germany). P-amino acids (AA) concentrations were measured by high-pressure liquid chromatography (HPLC) method using a Thermo Scientific Ultimate 3000 system, as earlier described [ 11 ]. Briefly, the samples were diluted 1.11x by adding 2 M Perchloric acid (HCIO 4 ) and then centrifuged at 14,000× g at 4 °C for 10 min.…”
Section: Methodsmentioning
confidence: 99%